In Situ Simulation to Mitigate Threats to Participation in a Multicenter Clinical Trial in High-Acuity, Low-Frequency Setting. Issue 1 (February 2019) - Chan, Steven; Babcock, Lynn; Geis, Gary; Frey, Mary; Robinson, Venita; Kerrey, Benjamin
Abstract : Introduction: Multicenter clinical trials of high-acuity, low-frequency emergencies are expensive and resource intensive. Current standards for trial preparation have significant limitations. Our objective is to describe our use of in situ simulation (ISS) to identify and mitigate threats to enrollment, protocol adherence, and patient safety in preparation for a multicenter clinical trial of antiepileptics for status epilepticus in the emergency department. Methods: This is a descriptive study of ISS conducted in the emergency department at a free-standing, academic pediatric institution. We designed two scenarios, one for an eligible and ineligible patient, to allow care teams to complete all study procedures. All study training was completed before the first ISS. Participants included physicians, nurses, patient care assistants, paramedics, research coordinators, and pharmacists. Ten-minute simulations were followed by 10-minute debriefings, led by trained facilitators using a standard template. Data on threats to enrollment, protocol adherence, and patient safety were recorded. Mitigation strategies were developed by the study team and local experts in ISS. Results: Ten of 18 planned simulations were conducted. Seven of 10 completed simulations were study eligible patients, with 73 total participants. Nine threats to enrollment and five to protocol adherence were identified. Five of 14 were also threats to patient safety. Mitigation strategies included creation of decision aid tools, targeted education during debriefings, adapting study material for use, and revision of status epilepticus treatment algorithm. Conclusions: The addition of ISS to standard preparation for a multicenter clinical trial facilitated the identification and mitigation of threats to study participation and patient safety. Abstract : Supplemental digital content is available in the text.